A Converter Based on Independently Inductive Energy Injection and Free Resonance for Wireless Energy Transfer - Lin Chen; Jianfeng Hong; Mingjie Guan; Zaifa Lin; Wenxiang Chen (Energies, 2019)
Strong coupling in an inductive power transfer (IPT) system will lead to difficulties in power control and loss of soft switching conditions. This paper presents an IPT system that can decouple the converter from the resonant network. In the proposed system, the energy transmission process is divided into energy injection stage and free resonance stage. In the energy injection stage, the inductor is separated from the resonance network, and the power source injects energy into the inductor independently. In the free resonance stage, the inductor is connected to the resonance network for resonating. As a benefit from the decoupling of the converter from the resonance network, the proposed IPT system is characterized by easy power control and soft switching operation. A prototype was built for experiments. The experimental results show that with a supply voltage of 300 V, coupling factor of 0.2, and load resistance of 10 Ω, the output power can be controlled nearly linearly by the time of the energy injection stage in a range of 40−60 μs, and the system works under soft switching conditions.